HUBUNGAN KONDISI FISIK RUMAH DAN PEKERJAAN DENGAN KEJADIAN TUBERKULOSIS PARU DI DESA BANDAR KHALIPAH KECAMATAN PERCUT SEI TUAN TAHUN 2015 - annisa febriana; nurmaini *; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACTTuberculosis remains a major global health problem, which causes pain in millions of people every year. One factor that also affects the pulmonary TB is a job. Type of job determine the risk factors that must be faced by every individual. Another important factor for pulmonary TB transmission is house. This study aims to determine the relationship of the physical condition of the house and work with the incidence of pulmonary TB in Bandar Khalipah, Percut Sei Tuan. This research’s design was Case Control with a total sample of 60 respondents, consisting of 30 sample cases, who were the patients with pulmonary tuberculosis that were recorded in recorded medical records in Puskesmas Bandar Khalipah, and 30 control samples that residents living around the house with pulmonary tuberculosis by matching with a case in point age and gender. Accourding to the result of this research, there was a significant differenec between the citizen’s house who suffer from pulmonary tuberculosis with the citizens who didn’t suffer from it. The data shows, that Odds Ratio Of over crowded 4,57, ventilation is 2,51, type of floor is ,70, lighting is 3,28, and humidity is 4,17 it is estimated that the physical condicition of citizen’s house (over crowing, ventilation, lighting and humidity) indicate that there is relation between the physical condition of the house with the prevalence of pulmonary tuberculosis in Bandar Khalipah, Percut Sei Tuan. Therefore, citizens should seek shelter and environmental health for healthful housing. Bandar Khalipah community health centre in order to conduct outreach about the terms of a healthful housing.Kata Kunci : Physical condition of house, Job, Pulmonary Tuberculosis